Overcoming Language Challenges of Open Source Appropriate Technology for Sustainable Development in Africa - (:unkn) unknown (My University, 2009)
Despite enormous efforts over the course of several decades, sustainable development on the African continent remains incompletely realized. Top-down methodologies have largely failed and many sustainable development organizations now support small-scale direct approaches, which provide the tools and knowledge necessary for people to help themselves. The new approach to sustainable development of open source appropriate technology (OSAT) builds on these successes. OSAT is a development method for traditional appropriate technologies (following Schumacher). The fundamental concept behind OSAT is that anyone can learn how to make and use AT free of intellectual property concerns, and can simultaneously add to the collective open source knowledge base by contributing ideas, observations, and experimental data. This approach to drive sustainable development is promising because the continuous peer review should result in better quality, higher reliability, more flexibility and of course less expensive (free) AT than conventional design/patenting. As OSAT is being developed largely in English, Africa’s many languages present a fundamental challenge to OSAT’s use for sustainable development on this continent. This paper provides potential solutions to this challenge by reviewing i) the ongoing merger between Appropedia (English) and Ekopedia (French), ii) systematic translations at the NGO Catalytic Communities, and iii) virtual service learning in languages. Despite enormous efforts over the course of several decades, sustainable development on the African continent remains incompletely realized. Top-down methodologies have largely failed and many sustainable development organizations now support small-scale direct approaches, which provide the tools and knowledge necessary for people to help themselves. The new approach to sustainable development of open source appropriate technology (OSAT) builds on these successes. OSAT is a development method for tr
Keywords: African Research